Preparation and Characterization of Chitosan–Durian Seed Composite Adsorbent for Tofu Wastewater Treatment - Silvia Devi Eka Putri; Endi Adriansyah; Rifqi Sufra; Nurul Asni; Yuyun Lusini; Anugrah Thoriq; Zidan Ashri Aksaronas; Saskia Eka Dian; M. Syaiful (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
The tofu industry generates wastewater containing high concentrations of total dissolved solids (TDS) and total solids (TS), posing significant environmental concerns. This study aimed to develop a chitosan-modified durian seed (Durio zibethinus) composite bioadsorbent for the removal of TS and TDS from tofu wastewater. The composite was characterized using scanning electron microscopy (SEM), X-ray fluorescence (XRF), and particle size analysis (PSA), followed by batch adsorption experiments at different adsorbent dosages. The initial wastewater contained 7,528 mg/L TDS and 9,139 mg/L TS. The composite exhibited superior adsorption performance compared with pristine chitosan, achieving a maximum TDS removal efficiency of 65.84%, reducing the TDS concentration to 2,572 mg/L, while TS removal reached 47.70%, with the final TS concentration decreasing to 4,780 mg/L at an adsorbent dosage of 1 g. Material characterization demonstrated that chitosan modification improved the composite morphology and physicochemical properties, thereby enhancing its adsorption performance. These findings indicate that the chitosan-modified durian seed composite is an effective, low-cost, and environmentally friendly bioadsorbent for tofu wastewater treatment. Furthermore, the utilization of durian seed waste as a bioadsorbent contributes to agricultural waste valorization and supports circular economy practices. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and Sanitation SDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production|SDG 13: Climate ActionSDG 15: Life on Land